Dinamika Mombolasuako di Sulawesi Tenggara: Perspektif Hukum Islam : - Ipandang (Al-Ulum, 2020)
This article examines the dynamics of the mombolasuako that emerge in Coastal Tolaki society of Southeast Sulawesi in the perspective of Islamic law. This dinamics was triggered by actions that come out of the traditions of Coastal Tolaki community. Where this society has a strict marriage tradition by holds fast to the principle of "married close to a close family" (endogamy). Even the costs incurred are very large. Therefore, this article was used a normative and sociological approach to explain the dynamics and paradigmatics of mombolasuako marriages. This article found that the mombolasuako action arises because it is formed from the paradigmatic side of the Tolaki community which was relatively incompatible with marital customs. In fact, from the perspective of Islamic law, mombolasuako is an action that falls into the category of sadd az-zariah actions, in which are: actions that originally had benefits, but instead led to obstructions.